Preliminary assessment of microcirculation in the ascending aorta in patients with normal and dilated ascending aorta using laser Doppler perfusion monitoring - Mikołaj Krysiak; Andrzej Łoś; Rafał Pawlaczyk; Mateusz Janeczek; Marcin Hellmann (European Journal of Translational and Clinical Medicine)
Background: Microcirculation within the ascending aortic wall, supplied by the vasa vasorum, is increasingly recognized as a potential factor in the pathogenesis of aortic aneurysms. However, in vivo assessment remains challenging. This pilot study aimed to evaluate ascending aortic microcirculation intraoperatively using Laser Doppler Perfusion Monitoring (LDPM). Material and methods: Twenty-four patients (18 males, 6 females) undergoing elective cardiac surgery were enrolled. LDPM was performed on the exposed ascending aorta prior to surgical manipulation. A probe was sutured to the aortic wall and perfusion was recorded in Perfusion Units (PU). A brief probe compression test was conducted to evaluate perfusion response. Results: The mean LDPM value was 281.58 PU (males: 339.94 PU; females: 139.86 PU). In males, LDPM negatively correlated with age (r = –0.593, p = 0.0121), whereas a moderate but non-significant correlation was noted with BMI (r = –0.303, p = 0.2366). No significant associations were observed with hypertension, diabetes, smoking, or aortic dilation. A paradoxical increase in PU during probe compression occurred in 54% of patients. Conclusions: LDPM provides real-time intraoperative assessment of aortic microcirculation. Age-related decline in perfusion may contribute to aortic wall vulnerability. Further studies with larger cohorts are needed to validate these findings.